(untitled) (Research, Society and Development, 2021)
Objective: To analyze the effectiveness of strengthening exercises for patients after anterior cruciate ligament injury through the analysis of indicators found in the literature. Methodology: This is a systematic literature review, such data used in the composition of this study were collected in the website’s database: PUBMED, and in journals and periodical books that have the theme of the study. The selected documents which refer to the theme, and which are published in the years 2016 to 2021, were excluded from case studies, incomprehensible studies, systematic reviews and with inadequate methodology, and which were described in an incohesive and inconsistent way to the proposed theme Results: Literature searches resulted in a finding of 1065 articles using the keywords “anterior cruciate ligament, muscle strengtheing”, but only 185 correlated with the theme of anterior cruciate ligament injury, of these 185 only 6 met all the inclusion criteria and directly described some strengthening exercise technique after anterior cruciate ligament injury, and in the Pedro scale analysis, it presented a result above 7. Conclusion: Progressive strength training is efficient for quadriceps and hamstring recovery, and eccentric resistance exercises open-chain, isokinetic and concentric aids in strengthening and activating neu romuscular muscles are efficient for recovery even in a late phase, intervention through strengthening exercises associated with other therapies for recovery from the post ACL condition increases the effects of the patient’s rehabilitation.